Impact of Stunting History on Adults: Literature Review - Permaida, Permaida (Poltekkes Kemenkes Tanjung Karang, 2023)
Stunting is the root of the problem that affects human growth and development. This problem starts from the growth of the fetus until the first 1000 days of life. If not addressed, it will have long-term impacts. This article aimed to determine the impact of a history of stunting on adults. This research method uses a literature review. Article searches using the Taylor and Francis, Science Direct, and Springer Link databases. Seven articles met the inclusion criteria. The research results showed that 28.5% of the articles were researched in developed countries and 71.5% in developing countries. However, there are no research articles from Indonesia. Researchers found the impact of a history of stunting on adults, including 87.5% of articles describing physiological consequences, 66.7% of all articles mentioning cognitive obstacles, and 57.1% of all articles evidencing psychosocial problems. In conclusion, the impact of a history of stunting on adults is confirmed and a polemic that must be addressed immediately. If left untreated, this will continue to happen, becoming a scary cycle and reducing the quality of human resources.